Utilization of Cinnamon Leaves (Cinnamomum burmannii, Blume) and Effectiveness Test as Mouthwash against Oral Microbes - Octora, Debi Dinha; Irwanto, Reno; Simarmata, Pratiwi Christa (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Oral health is an important aspect to pay attention to because it is part of the digestive system. Disorders in oral health function can impact other bodily health. The use of mouthwash is necessary to improve the cleanliness and health of the mouth, especially when brushing alone is not optimal. The active compounds in mouthwash enhance cleanliness and effectively inhibit the growth of pathogenic oral microflora. Cinnamon leaves have not been widely utilized and are often left unused or discarded. Previous research has been conducted on the potential of the compounds in cinnamon leaves. This research was carried out by determining the best essential oil content of cinnamon leaves through several preliminary treatments and varying distillation times. Active compounds such as cinnamaldehyde, L-linalool, and cinnamyl acetate were found in the cinnamon leaves, making them a potential ingredient for mouthwash formulation. The aim of this study is to produce an effective mouthwash that reduces the growth of pathogenic oral microflora using underutilized local materials. The mouthwash preparation method was modified from several active ingredient mouthwash preparation methods by varying the concentration of cinnamon leaf essential oil at 5%, 10%, and 15%. The formulations were then evaluated for organoleptic properties, stability, homogeneity, and antibacterial activity against S. mutans using the disc diffusion method. The results showed that the preparations remained physically stable and homogeneous during 30 days of storage at room temperature. The cinnamon leaf mouthwash exhibited antibacterial activity against S. mutans, with average inhibition zones of 15.25 mm, 19.06 mm, and 24.34 mm for formulations I, II, and III, respectively. Based on these results, it can be concluded that the cinnamon leaf mouthwash has the potential to inhibit the growth of S. mutans bacteria.